THE IMPACT OF LATE-NIGHT SOCIAL MEDIA USAGE TOWARDS COGNITIVE ENGAGEMENT OF FEMALE ENTREPRENEURS IN INDONESIA - Zipora Hana Sakura Parengkuan; Cynthia Anna Wijayanti (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
The trend of social media incremental usage has become increasingly visible in everyday life. Excessive usage of social media is a modern phenomenon that has several negative effects in the entrepreneurial realm, however it has received little attention in empirical study. Based on the stressor–strain–outcome model, this study intends to reveal that late-night social media usage might impact two psychological strains (technostress and life invasion) amongst female entrepreneurs and hence have an influence on their behavioural outcomes (cognitive engagement). The object of this research are female entrepreneurs in Indonesia from the small and medium sized enterprise sector (SMEs) that have used social media late at night. This study used a quantitative approach and non-probability purposive sampling as the sampling technique. There were 200 respondents obtained using an electronic questionnaire which was then processed using the PLS-SEM method using SmartPLS. The results indicated that late night social media usage significantly raises life invasion and technostress among female entrepreneurs. However, late night social media and the two psychological strains have positive impacts towards entrepreneurial cognitive engagement as opposed to negative. The results of this study are expected to provide new insights for female entrepreneurs about the benefits of social media usage to view social media usage as beneficial tool which brings advantages that could help their businesses remarkably. More toward older generation who have difficulties in utilizing social media in daily life regardless the businesses they have. In this digital era, it is important to keep up and learn more about social media to be able to follow the market movement and capture business’s opportunities posted through social media.